What Would the Younger Generation Give Up for a Better, More Sustainable Future? - Kolnhofer-Derecskei, Anita; Majláth, Melinda (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The UN defined sustainability as meeting the needs of the present without compromising the ability of future generations to meet their own needs. That partly means to satisfy the needs of the present and to live a happy and contented life. At the same time, this also means that we should give up remaining within the ecological limits of the Earth. This is one of the major challenges of our century. The PRME Youth Talks survey asked young people how they see the world: what they hope for and what they fear for the future. The questions included a block on what they would and would not give up for a better future. Among the responses were several issues related to sustainability. Based on 80 PRME interviews, this research aims to explore younger generations' opinions about conscious consumption. We found that young people are willing to sacrifice are material consumption, their free time and personal ambitions. This generation seems to be ready to work for a sustainable future.